Analisis Ancaman Keamanan Informasi Pada Insfrastruktur Teknologi di Universitas Bhayangkara Jakarta Raya - Farhan Maulana; Khalil Putra Pratama; Muhammad Fadillah; Muhammad Irfan Adji Wicaksono; Raka Kristianto (Journal of Informatic and Information Security, 2024)
Information security is a critical aspect in the digital era, especially for higher education institutions such as Universitas Bhayangkara Jakarta Raya. With the increasing use of information technology in learning and administrative processes, the potential for information security threats has also grown, ranging from cyberattacks to system vulnerabilities. This study aims to analyze various information security threats faced by the university’s technological infrastructure and evaluate the effectiveness of the implemented mitigation measures. The methodology used is a quantitative survey with respondents consisting of university students, collected through online questionnaires.The findings of this research indicate that the majority of respondents consider information security to be very important, with many reporting experiences of threats such as malware and phishing. Furthermore, the study found that although the university has a dedicated team to handle security incidents, there is still a need to improve infrastructure and awareness regarding information security. Recommendations include implementing machine learning technology for threat detection and enhancing training for the information security team to improve responses to evolving threats.